THE JOY OF ART IN THE EFL CLASSROOM - Schander, Claudia; Balma, Blanca M.; Massa, AgustÃn A. (European Scientific Journal, ESJ, 2014)
The need to motivate students in the EFL classroom has become an established area of research and discussion. Our work focuses on a more positive outlook on teaching and learning English, based on the assumption that we learn from information taken in through our basic natural senses. Based on Gardner’s (1993) Multiple Intelligence Theory, we present the idea that the use of our senses may help create a livelier atmosphere and cater for different learning styles (Oxford 1990). Therefore, we propose different tasks by introducing a range of artistic expressions, such as music, paintings, literature and films. In traditional learning environments (Nunan 1999), art and language learning seem to be at opposite ends of the spectrum in the quest to motivate students. However, we believe that these two fields do not necessarily stand apart and that their reciprocal virtues can invoke and provoke high levels of motivation that result in increased participation, especially one that will lead to meaningful text production. We will describe and carry out a selection of thoughtfully designed activities aiming at written and oral productions triggered by sensory stimuli. The input provided by a palette of artistic expressions will give students the pleasure of discovering how effectively they can express themselves both in written and oral language. As for teachers, they will be able to encourage their students to approach the language learning process in a mood of discovery and to exercise their imaginative powers freely.